Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI Di SDN 27 Ladang Hutan Baso - Helmila, Feni; Aprison, Wedra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research was motivated by several problems that the author found in class V of SDN 27 Ladang Hutan Baso. In the learning process there are students who are less actively involved in carrying out learning, such as many students who have difficulty understanding PAI learning, lack of student activity both physically and cognitively, monotonous learning, lack of student understanding of the material being studied, lack of student courage when appearing in front class, lack of student discipline in learning, learning is still teacher-centered which causes students to tend to be less active, and there are still many class V students who have not achieved maximum learning results so the quality of learning must be improved further. This research is a type of quantitative research with experimental methods. This research was located at SDN 27 Ladang Hutan Baso. The population in this study was 57 students. And the sample in this study was 38 students. The sampling technique used is random sampling technique. The instruments used in this research are tests and documentation. Based on the results of the analysis and discussion of the research data obtained regarding the influence of the Contextual Teaching Learning learning model, which is very influential on student learning outcomes in PAI subjects with a T-test calculation with a significance of 5% as can be seen if sig (2-tailed = 0.378) > 0.05 then H_o is accepted and H_a is rejected. So it can be concluded that there is an influence of the contextual teaching learning model on student learning outcomes in PAI subjects at SDN 27 Ladang Hutan Baso.  It is known that the average score for the control class is 83 and the average score for the experimental class is 85.